Applicability of rotary thermal wheels to hot and humid climates - H. M. D. P. Herath; M. D. A. Wickramasinghe; A. M. C. K. Polgolla; A. S. Jayasena; R. A. C. P. Ranasinghe; M. A. Wijewardane (Energy Reports, 2020)
Buildings in hot and humid climates spend more than 60% of the total energy cost for Air Conditioning and Mechanical Ventilation Systems (ACMV) to maintain the required thermal comfort for occupants. The required air conditioning load drastically increases with the fresh air demand of the conditioned space which leads to excessive energy bills for central air conditioning systems of buildings, particularly in hot and humid climates. Therefore, this study mainly focuses to investigate and evaluate the applicability of rotary thermal wheel to recover the energy available on the return air of the air handling unit (AHU) of the central air conditioning systems in hot and humid climates. The results reveal that, the percentage energy saving due to the rotary thermal wheel increases when the temperature and the relative humidity of outdoor fresh air increases, and also when Coefficient of Performance (COP) of the central chiller decreases. Moreover, case studies show that the simple payback period of a building which is supplied with 20% fresh air varies from 1.1 years to 4 years depending on the fresh air mass flow rate. Results reveal that the use of rotary thermals in the hot and humid climates is highly recommended.
Keywords: 330; Air conditioning; Air Handling Unit (AHU); Energy recovery; Hot and humid climates; Rotary thermal wheel